2022
DOI: 10.1155/2022/5476714
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Diagnosis of Alzheimer’s Disease in the Eastern Province of Saudi Arabia Using Computational Intelligence Techniques

Abstract: Alzheimer’s Disease (AD) is a silent disease that causes the brain cells to die progressively, influencing consciousness, behavior, planning ability, and language to name a few. AD increases exponentially with aging, where it doubles every 5-6 years, causing profound implications, such as swallowing difficulties and losing the ability to speak before death. According to the Ministry of Health in Saudi Arabia, AD patients will triple by 2060 to reach 14 million patients worldwide. The rapid rise of patients is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results showed that this model reduced the number of features from 21 to 16, with an AUC of 0.980, sensitivity of 94.0%, and specificity of 93.3%. After applying a forward feature selection technique, Olatunji et al [16] used SVM to construct a model for screening AD, achieving an accuracy of 95.56%, precision of 94.70%, and recall of 97.78%.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that this model reduced the number of features from 21 to 16, with an AUC of 0.980, sensitivity of 94.0%, and specificity of 93.3%. After applying a forward feature selection technique, Olatunji et al [16] used SVM to construct a model for screening AD, achieving an accuracy of 95.56%, precision of 94.70%, and recall of 97.78%.…”
Section: Related Workmentioning
confidence: 99%
“…Nonetheless, the proposed model in the current study utilized garbage classification data from Kaggle, as studies in [22,34] used the same data with CNN model and achieved accuracy of 82% and 86%, respectively. Furthermore, several computational intelligent methods are investigated for health informatics and public safety with promising results [39][40][41][42]. Therefore, this study proposed a deep learning model for waste management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To assess the performance of the proposed model on the given datasets, four measures are used: accuracy, F-score, recall, and precision. Further, intelligent methods are used in many health informatics [46][47][48][49][50], data visualization [51][52][53][54][55], and other related areas [56][57][58].…”
Section: Evaluation Metricsmentioning
confidence: 99%